Sistemas de información geográficos y sus incidencias en la prevención de desastres naturales en el cantón Montalvo. - Del Salto Cedeño, David Fernando (2023)
Geographic Information Systems (GIS) currently become one of the most useful main tools for risk analysis and prevention of natural disasters, because they have made it possible to carry out knowledge and risk prevention studies in order to determine probability, possible consequences and areas of probable impact upon the occurrence of threatening events. GIS also allow us to apply and design different multi-criteria methodologies according to the type of threat to be evaluated and give us results such as: Total risk, vulnerability. It should be noted that a Geographic Information system is a Risk Management tool, with emphasis on the prioritization and identification of the various areas addressed in the Canton of Montalvo through GIS, thereby allowing the identification of priority and secondary streets and sectors. In addition, the incorporation of communities most vulnerable to seismic events and floods is proposed, defining possible reference places and identifying risks. The primary purpose of the research is to provide a support mechanism for the subsequent construction of a tool that has all the necessary elements so that the municipality of the Montalvo canton can keep a record in real time of everything that happens in the local territory. Geographic Information Systems (GIS) are very powerful tools that allow, on the one hand, to work on territorial planning - in the implementation of levels of prevention against the threats to which a territory is exposed and thus provide efficient responses to upon the occurrence of an emergency or catastrophe. With these references, among the main results found, it was determined that the detailed areas have a high probability of flooding in the winter season and the vulnerability factors with the highest incidence are the loss of houses and crops such as diseases and material and human losses. Due to all this information, the need to have a geographic information system (GIS) as a basis for sustainable development of the Montalvo canton, province of Los Ríos is evident, since through its implementation actions can be developed to reduce vulnerabilities. disasters and, consequently, the risks faced by them.